2007
DOI: 10.1542/peds.2007-0398
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Management of Family Psychosocial Problems at Low-Income Children's Well-Child Care Visits: The WE CARE Project

Abstract: Brief family psychosocial screening is feasible in pediatric practice. Screening and provider training may lead to greater discussion of topics and contact of community family support resources by parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
251
2
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 242 publications
(269 citation statements)
references
References 30 publications
3
251
2
13
Order By: Relevance
“…The 15% difference between groups was thought to be clinically significant and feasible based on our previous study. 19 An intention-to-treat approach was used to compare intervention and control groups on study outcomes. Generalized mixed-model regressions were used to estimate the differences in covariates between groups and to test direct intervention effects on primary and secondary outcomes.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%
“…The 15% difference between groups was thought to be clinically significant and feasible based on our previous study. 19 An intention-to-treat approach was used to compare intervention and control groups on study outcomes. Generalized mixed-model regressions were used to estimate the differences in covariates between groups and to test direct intervention effects on primary and secondary outcomes.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%
“…The WE CARE survey 78 is a brief set of questions that alerts the pediatrician to families experiencing stress related to poverty. In the policy statement "Promoting Food Security for All Children, " the AAP recommends the use of a 2-question survey that has a high sensitivity to detect food insecurity.…”
Section: Early Identifi Cation Of Families In Need Of Servicesmentioning
confidence: 99%
“…One example, the Well Child Care, Evaluation, Community Resources, Advocacy, Referral, Education Program, is a clinic-based screening, diagnosis, and referral program to help practices assist families living in poverty with unmet basic needs. 58 This program relies on a brief screening tool to determine areas of need and a resource book with tear-out information sheets for families. In a recently published randomized controlled trial, improvements for families were found with respect to key SDH, including adequate housing, fuel assistance, child care, and employment.…”
Section: Connecting Screening and Diagnosis To Actionmentioning
confidence: 99%